Identification of risk factors for high-risk dedifferentiation in papillary thyroid carcinoma and construction of discriminative model - Liu, Xiang; Zhu, Qiao-li; He, Zi-yi; Shu, Jing-de; Xiang, Cheng (Frontiers in Oncology, 2025)
ObjectiveWe initially found that the thyroid differentiation score (TDS) was associated with the prognosis of papillary thyroid carcinoma (PTC) patients. Therefore, this study aimed to investigate the influencing factors and construct a discriminative model of high-risk dedifferentiation, and to explore the possible mechanisms.MethodsData were sourced from the TCGA database. The influences of the TDS, tumor mutation burden, and immune score on the progression-free interval (PFI) were assessed by the Kaplan-Meier method and multivariable Cox regression. Then, logistic regression analyses were utilized to explore the factors of dedifferentiation and a nomogram model was conducted. Additionally, differentially expressed genes (DEGs) were identified using RNA sequencing data, while their regulatory pathways were determined by the Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis. Finally, the differential expression of key genes of major pathways was explored.ResultsThis study included 391 PTC patients. After analyzing the influences of the three indicators on survival, only TDS showed an association with PFI. Multivariable logistic analysis revealed that the disease duration and PTC subtypes influenced dedifferentiation. The nomogram model based on these two variables showed improved discriminative capability. The study identified 17 overlapping DEGs associated with the dedifferentiation and three primary enrichment pathways, with complement and coagulation cascade pathways being the most significant (P<0.001). The central gene was CD55, which showed high expression in high-risk dedifferentiated and tall cell PTC, and the expression level increased as the disease progressed.ConclusionThis research may contribute to promising identifying high-risk dedifferentiated PTC and also provide a potential therapeutic target.